Incorporating Wave-ViT for Breast Cancer Diagnosis Using MRI Imaging - Sahil Mahey; Hamid Usefi (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Breast cancer remains one of the leading causes of mortality among women globally, and early detection is critical for improving survival rates. Breast MRI, the most sensitive imaging modality for detection, often involves manual review of numerous slices, which is time-intensive and prone to human error. Machine learning (ML) algorithms offer a transformative solution by automating this process, improving efficiency, and enhancing diagnostic accuracy.